2018
DOI: 10.1002/jcp.27475
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous nanoparticles and endogenous crystalline molecules as danger signals for the NLRP3 inflammasomes

Abstract: Inflammasome mechanisms are involved as some of the pathways of sterile inflammation. Inflammasomes are large multiprotein complexes in the cytosol and are a key system for the production of the pivotal inflammatory cytokines, interleukin (IL)-1β and IL-18, and inflammatory cell death called pyroptosis. Although a number of inflammasomes have been described, the nucleotide-binding oligomerization domain-, leucine-rich repeat-, and pyrin domain-containing 3 (NLRP3) is the most extensively investigated inflammas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 135 publications
(316 reference statements)
2
49
0
Order By: Relevance
“…Gallo and Gallucci, 2013, first alluded to the idea of NP‐associated molecular patterns (NAMPs) as studies demonstrated that NPs could be recognized by immune cells, a concept that continues to be supported by a growing body of evidence . As previously mentioned in this review, NPs have been shown to directly bind SRs on macrophages, both class A and class B, inducing phagocytosis and/or NLRP3 inflammasome activation.…”
Section: Nps As Molecular Patternsmentioning
confidence: 95%
See 4 more Smart Citations
“…Gallo and Gallucci, 2013, first alluded to the idea of NP‐associated molecular patterns (NAMPs) as studies demonstrated that NPs could be recognized by immune cells, a concept that continues to be supported by a growing body of evidence . As previously mentioned in this review, NPs have been shown to directly bind SRs on macrophages, both class A and class B, inducing phagocytosis and/or NLRP3 inflammasome activation.…”
Section: Nps As Molecular Patternsmentioning
confidence: 95%
“…Exposure to NPs has been shown to cause release of various endogenous danger signals—some as a result of oxidative damage and mitochondrial dysfunction, others as a result of lysosomal rupture. Whereas apoptosis is a common fate of cells exposed to NPs, other more inflammatory forms of cell death have been shown to occur as well; NP‐induced release of mitochondrial and lysosomal DAMPs can trigger a highly inflammatory mode of cell death termed pyroptosis, whereas disruption in the cell membrane through either direct cell‐NP interactions or through oxidative damage can lead to necrosis . In this way, DAMPs produced as a result of NP exposure can be released into the extracellular compartment following cell death via pyroptotic or necrotic pathways, acting as endogenous danger signals to nearby cells.…”
Section: Np Exposure Leads To Release Of Endogenous Danger Signalsmentioning
confidence: 99%
See 3 more Smart Citations